Pericles en Lima: el virrey Manso de Velasco, el terremoto y su imagen pública - Barriga Calle, Irma (2022)
This article explores how the Viceroy Count of Superunda built an image of power in the wake of the 1746 earthquake and had painting as a magnificent ally that contributed to consolidate the absolutism of the regime. Faced with the aftermath of the disaster that befell the capital city, he had not only to restore the viceregal power, but also to reestablish the colonial pact, appealing to different converging discourses that would show him as an enlightened ruler and as a protective and magnanimous father. The strong persuasive power of painting played a key role in this.